KEBAHAGIAN (HAPPINESS) PADA ORANG TUA YANG MENGALAMI SINDROM SARANG KOSONG - Patria Mukti; Endang Widyastuti (Jurnal Psikohumanika, 2019)
Human beings in their lives undergo an endless process and are constantly developing, from the prenatal period to old age. In the final phase or the elderly, some parents experience a period when they will be abandoned by their children for college, work or family, called the empty nest syndrome. This syndrome is closely linked to sadness, even though humans really want to find happiness in life. The purpose of this study is to understand and describe the meaning of happiness felt by parents with empty nest syndrome. The informants in this study are parents who live alone or alone with a partner The research method used in this study is a qualitative research method. The data collection method used in this study is to use an open questionnaire according to which informants are free to answer questions freely, according to their own understanding, logic, terms and language style. The informants in this study were taken by reasoned sample. The informants in this study were parents who experienced empty nest syndrome. 30 The analysis of the data in this study used triangulation. The results showed that the happiness of parents who experience the empty nest syndrome is more family-based, can come together, receive love, attention and prayer. The people who play the biggest role in happiness are the essential families such as spouses, children and grandchildren